Evaluation of the Effect of Pheophytin A on Electroshock-Induced Seizures in Experimental Animals - Almuthaybiri, Qasem H; Al-Rasheedi, Eissa E; Elsisi, Hossam A (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: An epileptic seizure is a transient occurrence of signs and/or symptoms due to abnormal excessive or synchronous neuronal activity in the brain. Approximately, 5–10% of the people have at least one kind of seizure, with more chance of occurrence in early childhood and late adulthood. There are many drugs used in seizures such as phenytoin and valproate sodium, so the main objective of current study was evaluated the efficacy of Pheophytin A compared to Valproate sodium on electroshock-induced seizures in experimental mice. Materials and Methods: The total number of 18 mice were used after divided into 3 groups in which each group was 6 mice. The first group, which is control, was received injection with distilled water. The second group was standard reference which received valproate sodium at dose of 300 mg/kg. The third group was test group which received 20 mg /kg of pheophytin A. Maximum electrical shocker was used to induce seizures. Results: The present study showed that pheophytin-A group had significantly reduced duration of seizures after 30 min of injection as compared to valproate sodium group. Valproate sodium produced more reduction in duration of seizures than pheophytin-A. Conclusion: The Pheophytin A showed antiseizure effect using maximal electrical shocker, so that it may be used in the future for treatment of seizures after further investigations.
Keywords: Seizures; Pheophytin A; Valproate sodium; Maximal electroshock seizure; In vivo